Forest preservation in a changing climate : REDD+ and indigenous and community rights in Indonesia and Tanzania - Jodoin, Sébastien, 1982- (Cambridge University Press, 2017)
"This book provides a comprehensive socio-legal examination of how global efforts to fight climate change by reducing carbon emissions in the forestry sector (known as REDD+) have affected the rights of indigenous peoples and local communities in developing countries. Grounded in extensive qualitative empirical research conducted globally, the book shows that the transnational legal process for REDD+ has created both challenges and unexpected opportunities for the recognition and protection of indigenous and community rights. It shows that pursuit of REDD+ has resulted in important variations in how human rights standards are understood and applied across multiple sites of law, with mixed results for indigenous peoples and local communities. With its provocative findings, interdisciplinary research design, and analytical framework, this book will make a valuable contribution to the study of the influence of transnational legal processes in a globalizing world. This title is also available as Open Access"--